(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The article deals with the methods of study tense verb forms of perfect and imperfect aspects on Ukrainian lessons with first-year foreign students of all specialties. The kinds of exercises for actualization, intensification, systematization, generalization, consolidation of foreign students’ knowledge about tense and aspect verb categories are proposed.